Improving Student Learning Motivation Through the Application of the Games for Understanding Teaching Model in Football Learning - Muhammad Agus Nurfalah; Indra Jati Kusuma; Didik Rilastiyo Budi; Kusnandar Kusnandar (Physical Activity Journal (PAJU), 2026)
This study aimed to determine the effect of the Teaching Games for Understanding (TGFU) learning model in soccer instruction on the learning motivation of seventh-grade students at SMP Negeri 8 Purwokerto. Physical education learning in junior high schools is often dominated by conventional, teacher-centered approaches, which tend to limit student participation and result in low learning motivation. The TGFU model is a game-based learning approach that emphasizes tactical understanding before mastering technical skills, thereby encouraging active student involvement and enhancing learning motivation. This study employed an experimental method with a one-group pretest–posttest design. The research sample consisted of 32 students from class VII H selected using a cluster random sampling technique. The research instrument was a learning motivation questionnaire that had been tested for validity and reliability. Data analysis was conducted using normality and homogeneity tests, followed by hypothesis testing using a paired sample t-test with the assistance of the SPSS program. The results showed an increase in students’ learning motivation after the implementation of the TGFU model, as indicated by the difference between pretest and posttest scores. The hypothesis test produced a significance value of 0.000 (p < 0.05), indicating that the implementation of the TGFU learning model had a significant effect on students’ learning motivation. Therefore, the TGFU learning model can be considered an effective alternative strategy in physical education learning to improve students’ learning motivation in soccer instruction at the junior high school level.